Service Quality as a Mediator of Customer Complaint Behaviour and Customer Loyalty - Osarenkhoe, Aihie; Komunda, Mabel Birungi; Byarugaba, Jotham Mbiito (International Review of Management and Marketing, 2017)
Aims to examine the mediating role of service quality in customer complaint behaviour and customer loyalty. Adopts a quantitative cross-sectional research design and uses the MedGraph program, Sobel tests and the Baron and Kenny method to test for mediation effect of service quality on the relationship between customer complaint behaviour and customer loyalty. Service quality is a significant mediator in the relationship between customer complaint behaviour and customer loyalty of Ugandan mobile phone subscribers. Adding service quality to the relationship boosts the relationship between customer complaint behaviour and customer loyalty by 45 percent among the mobile phone subscribers studied. Findings suggest that when service quality is low, a high level of customer loyalty may not be attained among mobile phone subscribers. Managers, policy-makers, and mobile telephone companies should advocate and strive for improvements across all dimensions of service quality to boost the loyalty of cell phone customers. This study is the first to test the mediating role of service quality in the relationship between customer complaint behaviour and customer loyalty among mobile phone subscribers in a developing nation context. Contributes to the positive significant influence of service quality in enhancing the level of customer loyalty based on customer complaint behaviour. Keywords: Customer Complaint Behaviour, Service Quality, Customer Loyalty JEL Classifications: D1, L15